Formação contínua nas práticas sociais de linguagens dos professores do campo no polo educacional de Tessalônica em Irituia /PA. - FREITAS, Maria Jacione da Silva (2023)
This research came from the need to analyze how continuos education occurs in the context of social language practices in the educational pole Tessalônica in Irituia- PA and also to strengthen the pedagogical practices of countryside teachers, from the organization of workshops and the production of a pedagogical notebook with the participation of the teachers of that pole, to support the portuguese language classes in 2nd year elementary school classes. Thus, we methodologically opted for a qualitative approach. The data collection was done by means of a focus group and literature review, it was based in authors who helped us understand the peasantry, countryside education and social practices of language. The locus of research was the educational pole Tessalônica, located in the village of Tessalônica, in Irituia/ PA. Eight teachers participated in the research, who made up the focus group, emphasizing that it was an experience that allowed us to verify the pedagogical practices in the context of social language practices, with more interaction. The survey results revealed the need for continuing education, as well as pedagogical material that dialogues with the reality of the countryside. Thus, based on the needs presented by the teachers, some interventions were carried out. The first intervention took place through three workshops, all mediated by the researcher. In addition to the workshops, an educational product was built with activities to help teachers of the second year of elementary school in dialogue with the local contextualization and with freedom to adapt, when necessary. The product presents ten activities to work with country students, which are also available on Youtube. The research was of great relevance, because it allowed not only to prove, scientifically, the hypotheses raised, but still contributed by involving the community in the training. It can be inferred that there is still a need for further studies on the subject, so that training is not restricted to teachers, and yes, to other subjects in the countryside.